Decline of Indian Parliament: The missing Debates: Exploring the Deterioration and Solutions for Indian Parliamentary Debates (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The idea of Democracy rests upon the principle of people’s participation in Decision making. It is a form of government in which the people have the authority and the choice to choose their representative. India being a parliamentary democracy people choose their representatives to the parliament and these representatives are responsible for putting forward the interests of people in the parliament. The Parliamentary democracy is a platform where the government of the day is held accountable for its actions, policies. It provides people an opportunity where the representative of people can advocate about people’s Aspirations, needs. This institution as a whole where Debates, discussion are an integral part of it, benefits the society with informed decision making and better policy alternatives. But in the recent times we have seen the Deteriorating picture of Indian parliament where procedural principles of parliamentary democracy are thrown out the window by the Parliamentarians. We are not paying attention to the things which were at some point considered biggest cornerstone of our democracy (debate, discussion, dissent, participation). The study highlights the recent trends of Indian parliamentary debates, reasons for the decline of Indian parliament and the suggestions to improve.